WORK LIFE BALANCE DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI DI DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KABUPATEN TANGERANG: WORK LIFE BALANCE AND ORGANIZATIONAL COMMITMENT TO EMPLOYEE PERFORMANCE AT THE ENVIRONMENT AND HYGIENE OFFICE OF TANGERANG REGENCY - Ihwan Satria Lesmana; Rani Sri Sumarsih; Listiawati Listiawati; Diah Permata Sari (Yayasan Education and Social Center, 2023)
The aim in writing this research was to determine the effect both partially and simultaneously between work life balance and organizational commitment on employee performance at the Tangerang Regency Environmental and Sanitation Service. The method used is descriptive analytic method with a quantitative approach with a sample of 53 respondents from 113 employees as a population. The results obtained partially for the work life balance variable are known to be -tcount < -ttable, namely (-2.084 < -2.008), so that it can be explained that Ho is rejected and Ha is accepted, as well as for the organizational commitment variable, it is known that the value is tcount > ttable, namely 11.703 > 2.008, so it can be explained that Ho is rejected and Ha is accepted. The same thing also happens simultaneously to both variables, it is known that the value of Fcount > Ftable (79.502 > 3.18), and it can be explained that Ho is rejected and Ha is accepted. Based on the research conducted, the results obtained were that, partially or simultaneously, work life balance and organizational commitment had an effect on employee performance at the Tangerang District Environmental and Sanitation Service